2020
DOI: 10.2355/isijinternational.isijint-2020-012
|View full text |Cite
|
Sign up to set email alerts
|

Gas Permeability Evaluation of Granulated Slag Particles Packed Bed during Softening and Melting Stage with Fanning’s Equation

Abstract: Negative effect from low coke rate operation at cohesive zone is obvious because it makes thinning of coke slit thickness. Correct knowledge about gas permeability of cohesive layer is becoming more and more important. In order to precisely understand cohesive behaviour, a softening and melting simulator under rapid heating and quenching conditions was applied for clarify a determinant factor of gas permeability behaviour. To focus on softening and melting behaviour, granulated slag particle bed layer without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A softening and melting simulator 2,10) can achieve to high speed temperature control over 1 000°C/min of sample packed bed by combination of infrared gold image furnace heating and dry-quenching chamber. Temperature distribution in a sample chamber, 30 mm inner diameter and 40 mm inner height, was confirmed within ± 5°C during radiation of infrared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A softening and melting simulator 2,10) can achieve to high speed temperature control over 1 000°C/min of sample packed bed by combination of infrared gold image furnace heating and dry-quenching chamber. Temperature distribution in a sample chamber, 30 mm inner diameter and 40 mm inner height, was confirmed within ± 5°C during radiation of infrared.…”
Section: Methodsmentioning
confidence: 99%
“…The deformation and melting cause clogging a gas flow passes in iron burden's layer, and this severe situation for gas flow makes bigger gas pressure drop values. Especially, Ohno et al 2) indicated that an effective gas path shape in cohesive zone could be a dominant factor for stable gas flow. Natsui et al 3) estimated the gas pass structure using numerical simulation based on Smoothed Particle Hydrodynamics method.…”
Section: Introductionmentioning
confidence: 99%
“…In most transport phenomena analyses, the void space in the packed bed is assumed to have a continuous structure of circular tubes with various diameters in the flow direction. 16,35) The pressure drop, ΔP, per unit length, L, is equivalent to the energy loss due to the shear stress acting on the tube wall surface. The shear stress corresponds to the frictional force per unit surface area applied to the fluid on the tube wall surface.…”
Section: Void Morphology and Gas Permeabilitymentioning
confidence: 99%
“…evaluated void distribution using computer tomography scanning and Fanning's equation, highlighting a strong relationship between the capillary force balance between molten slag and graphite and maximum pressure drop. [30] Mitra et. al.…”
Section: Introductionmentioning
confidence: 99%